Anxiety and depression level among pregnant women in an obstetrics and gynaecology clinic in Hospital Universiti Sains Malaysia (Hospital USM) - Tekat, Nor Hashimah (Universiti Sains Malaysia, 2013)
Anxiety and depression are mood changes that occur during pregnancy. The level of anxiety and depression of pregnant women may influence by the socio-demographic and clinical factors. A cross-sectional study conducted to determine the effect ol socio demographic and clinical factors during pregnancy period on anxiety and depression levels of the pregnant women. Data collected using self-administered questionnaire. The anxiety and depression level investigated using Hospital Anxiety and Depression Scale (HADS). 120 pregnant women that received treatment in antenatal clinic were recruited as respondents. Statistical analysis carried out using SPSS program Version 20. Majority (89.0%) of all respondents was suffering from severe anxiety while a few respondents had mild anxiety (5.0%). 35.0% of respondents reported had mild depression, in which only 23.3% of respondents were having severe depression. The data were assessed using frequency, percentages, standard deviations. Independent / test and One Way ANOVA test. The result showed no association between socio-demographic and clinical factors with the level of anxiety and depression among pregnant women with value of/? < 0.05. There was demographic and clinical factors during pregnancy period on Anxiety and depression are no positive correlation between socio-deinographic and clinical factors with the level of anxiety and depression during pregnancy. The information on the level of anxielx and depression among pregnant women was important in order to help them improve their emotional and psychological health throughout the pregnancy.